Exploring the Impact of Leucocyte Ig-like Receptor B1 on TNIP1 Protein Expression in Immune Effector Cells - Murad Ali, Tania Khattak, Azka Afzal, Akhtar Nawab, Isma Ali, Fawad Khalid (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Leucocyte Immunoglobulin-like Receptor B1 (LILRB1), also known as Immunoglobulin-like Transcript 2 (ILT2) or CD85j, is an inhibitory receptor that plays a crucial role in regulating immune effector cell activity. LILRB1 exerts its inhibitory function through Immunoreceptor Tyrosine-based Inhibitory